A Strategy for Weight Loss and Weight Management - Review - Czyżnikiewicz, Adrianna; Rulewska, Natalia Maria; Siemko, Jakub; Filip Grabowski,; Neska, Dagmara; Prystacka-Szar, Dominika; Bujak , Magdalena; Waśniowska, Magdalena; Stołowski, Wenancjusz; Stadler-Szajda, Justyna (Journal of Education, Health and Sport, 2025)
Introduction: Obesity is the excessive accumulation of fat tissue in the body, which has broad and serious health consequences. It has also become an increasingly significant issue in today's world. Aim: The aim of this article is to review the existing weight loss methods, their effectiveness, and the long-term maintenance of a healthy body weight. Review Methods: A comprehensive analysis of research papers available on PubMed and Google Scholar was conducted using the following search terms: obesity, obesity causes, obesity treatment, weight gain, weight loss, weight loss maintenance. Conclusion: Weight loss is a complex issue that requires an interdisciplinary and individualized approach for each case. Long-term weight maintenance mainly relies on lifestyle and habit changes.